Use of Dexmedetomidine for Preventing Pain on Propofol Injection: A Double Blinded Placebo Controlled Study (Anwer Khan Modern Medical College Journal, 2019)
Background and aim of study: Propofol is a commonly used drug for general anesthesia. It can irritate the skin, mucous membrane and venous intima. The main drawback is the pain during intravenous injection.  Aim of this prospective randomized study is to observe the efficacy of intravenous dexmedetomidine as  pretreatment for the prevention of pain caused by the propofol injection.Methods: A total of 80 adult patients were selected in this study with either sex, ASA (American Society of  Anesthesiologists) grade I and II, scheduled for routine elective surgical procedure under general anesthesia. The patients enrolled were divided randomly into two groups of 40 patients each. Group received 0.25 mcg of intravenous dexmedetomidine in 5 ml. Group II (placebo group) received 5 ml of  0.9% intravenous normal saline one minute before injection of propofol. The patients were asked to report  their pain during injection of propofol according to the McCririck and Hunter scale.Results: The incidence of pain experienced in dexmedetomidine group was 35% patients and in saline  group was 70% patients (p